2018
DOI: 10.3390/cells7100144
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Emulsion Inhibits the Late Apoptosis/Cardiotoxicity Induced by Doxorubicin in Rat Cardiomyoblasts

Abstract: This study aimed to examine the effect of lipid emulsion on the cardiotoxicity induced by doxorubicin in H9c2 rat cardiomyoblasts and elucidates the associated cellular mechanism. The effects of lipid emulsion on cell viability, Bax, cleaved caspase-8, cleaved capase-3, Bcl-XL, apoptosis, reactive oxygen species (ROS), malondialdehyde, superoxide dismutase (SOD), catalase and mitochondrial membrane potential induced by doxorubicin were examined. Treatment with doxorubicin decreased cell viability, whereas pret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 39 publications
(87 reference statements)
6
24
0
Order By: Relevance
“…In a clinical setting, Zhao and Zhang (2017) demonstrated that Dox administration activated cell death pathways in the hearts of cancer patients within hours of intravenous administration. Likewise, Subbarao and colleagues (2018) reported that H9c2 cardiomyoblasts treated with Dox had a significant increase in late apoptotic cells. Accordingly, our findings revealed that chronic Dox exposure significantly accelerates the rate of apoptosis in the cardiac and breast cancer cells.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…In a clinical setting, Zhao and Zhang (2017) demonstrated that Dox administration activated cell death pathways in the hearts of cancer patients within hours of intravenous administration. Likewise, Subbarao and colleagues (2018) reported that H9c2 cardiomyoblasts treated with Dox had a significant increase in late apoptotic cells. Accordingly, our findings revealed that chronic Dox exposure significantly accelerates the rate of apoptosis in the cardiac and breast cancer cells.…”
Section: Discussionmentioning
confidence: 92%
“…Although a direct link between antioxidants and the modulation of cancer immunoediting has not been fully established, evidence suggests that flavonoids may be able to modulate immunoediting processes like restoring cancer immune surveillance which may be helpful in eradicating cancer cells ( Bhattacharyya et al., 2010 ; Bose et al., 2015 ). Additionally, such flavonoids have been demonstrated to play a crucial role in mitigating the cardiotoxic effects inferred by Dox administration ( Bast et al., 2007 ; Sun et al., 2007 ; Chang et al., 2019 ). In the case of Pin, its ability to regulate inflammatory cytokines, improve mitochondrial function whilst inhibiting platelet aggregation and mitigating apoptosis in the cardiac muscle makes it a suitable candidate in the prevention of Dox-induced cardiotoxicity ( Saad et al, 2015 ; Shen, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Human umbilical vein endothelial cells (HUVECs, EA.hy926 cells, American Type Culture Collection, Manassas, VA, USA) were cultured in Dulbecco's modified Eagle's medium (HyClone, GE Healthcare, UT, USA) supplemented with 10% heat-inactivated fetal bovine serum (Gibco, Life Technologies, NY, USA), 2 mM l-glutamine, 100 U/ml penicillin, and 100 µg/ml streptomycin as previously described [20,21]. Cells were plated in a 100-mm culture dish and incubated at 37°C in a humidified atmosphere containing 5% CO2.…”
Section: Cell Culturementioning
confidence: 99%
“…Western blot analysis was carried out as described previously [18,19,21]. Cytosolic and membrane fractions were isolated from cells using a Mem-PER ® eukaryotic membrane protein extraction reagent kit (ThermoFisher Scientific, MA, USA) according to the manufacturer's instructions.…”
Section: Western Blot Analysismentioning
confidence: 99%
“…LE is well-known as a nonspecific antidote in medicine, in particular for bupivacaine-induced cardiotoxicity [6]. LE accelerates recovery from bupivacaine toxicity in isolated rat heart [7], inhibits apoptosis and cardiotoxicity induced by bupivacaine or doxorubicin in rat cardiomyoblasts [8,9], reduces bupivacaine content, and increases cardiac bupivacaine washout [7,10]. The protective mechanisms of LE on bupivacaine-induced cardiotoxicity have been generally thought to be lipid sink, lipid shuttle, fatty acid supply, reversal of mitochondrial dysfunction and cardiac Na + channel blockade, inhibition of nitric oxide release, and inotropic effects [11].…”
Section: Introductionmentioning
confidence: 99%